In Situ Observation of γ′ Phase Transformation Dynamics During Selective Laser Melting of CMSX‐4. Issue 11 (3rd May 2021) - Wahlmann, Benjamin; Krohmer, Erwin; Breuning, Christoph; Schell, Norbert; Staron, Peter; Uhlmann, Eckart; Körner, Carolin
Abstract : Additive manufacturing (AM) of superalloys has been attracting increasing interest. While most studies focus on the processability and mechanical properties of the finished product, it is also necessary to understand the phase transformations during the consecutive melting processes. Herein, the precipitation and dissolution of the γ′ phase in the Ni‐base superalloy CMSX‐4 in a selective laser melting process is reported. These phase transformations are studied in situ by small‐angle X‐ray scattering (SAXS) during AM. Concurrent wide‐angle X‐ray scattering (WAXS) provides information on the evolution of lattice parameters and temperature during the process. Additional thermal and thermodynamic simulations are carried out to support the experiments. The investigations are focused on the influence of different beam scanning strategies as well as the effect of laser power and scanning speed on the phase transformation dynamics. Due to the high cooling and heating rates inherent to AM, phase transformations occur far off equilibrium. Both precipitation and dissolution of γ′ phase are observed. The scan strategies are shown to have a considerable effect on the phase transformation dynamics, which exceed the impact of the beam parameters. The capability of combined SAXS and WAXS for the in situ study of phase transformations in AM processes is demonstrated. Abstract : Phase transformations during additive manufacturing of the nickel‐base superalloys CMSX‐4 are measured in situ using small‐angle and wide‐angle X‐ray scattering. Supported by thermal simulations, it is shown that the phase transformations occur highly off‐equilibrium. X‐ray scattering allows the qualitative observation of formation and dissolution of the γ′ phase within the solidified material during the deposition of successive layers.